2016
DOI: 10.1186/s12885-016-2539-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of patient-matched malignant and normal primary cell cultures from clear cell renal cell carcinoma patients: clinically relevant models for research and personalized medicine

Abstract: BackgroundPatients with clear cell renal cell carcinoma (ccRCC) have few therapeutic options, as ccRCC is unresponsive to chemotherapy and is highly resistant to radiation. Recently targeted therapies have extended progression-free survival, but responses are variable and no significant overall survival benefit has been achieved. Commercial ccRCC cell lines are often used as model systems to develop novel therapeutic approaches, but these do not accurately recapitulate primary ccRCC tumors at the genomic and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 38 publications
1
29
0
2
Order By: Relevance
“…Functional studies based on model systems to recapitulate genetic and phenotypic characteristics of the patient profile such as patient‐derived xenograft (PDX)/tissue grafts (TG), organoids and patient‐derived cultures that have recently been established from RCC . TG models were generally well‐characterized based on histology, gene expression and genomics, and are known to retain regional ITH . TG models only allow for small scale drug testing studies, however, may recapitulate the drug responsiveness in patients .…”
mentioning
confidence: 99%
“…Functional studies based on model systems to recapitulate genetic and phenotypic characteristics of the patient profile such as patient‐derived xenograft (PDX)/tissue grafts (TG), organoids and patient‐derived cultures that have recently been established from RCC . TG models were generally well‐characterized based on histology, gene expression and genomics, and are known to retain regional ITH . TG models only allow for small scale drug testing studies, however, may recapitulate the drug responsiveness in patients .…”
mentioning
confidence: 99%
“…Another issue with these organoids is the absence of nerves, blood vessels, and immune cells in the system. For example, a big difference in transcriptional profiles between VHL -mutant cells and their matched primary tumour specimens was observed by Lobo and colleagues 55 . However, further analysis indicated that the differentially expressed genes in the tumour component were mainly involved in immune functions, meaning that these genes were lost in VHL -mutant cultures owing to the absence of the immune cells.…”
Section: Development Of Organoidsmentioning
confidence: 91%
“…Prostate organoids can be derived from nonmalignant human and mouse prostate stem cells and mimic the morphology of a nonmalignant prostate. The use of patient-derived organoids to study cancers is expanding, with studies in bladder 50 , prostate 53 , kidney 54,55 , pancreatic 44 , and colorectal cancers 56 already published (FIG. 1b).…”
Section: Development Of Organoidsmentioning
confidence: 99%
See 2 more Smart Citations